The impact of odour on laundering behaviour: an exploratory study. Issue 1 (2nd January 2020) - McQueen, Rachel H.; Moran, Lori J.; Cunningham, Cassandra; Hooper, Peter M.; Wakefield, K. A.-Mariko
ABSTRACT: Detectable odour within clothing may influence how clothing is washed, leading consumers to make less sustainable choices than those for non-odorous clothing. This study was carried out to begin to explore the impact perceived odour may have on consumers' laundering practices. Through a questionnaire distributed online it was found that half of the respondents reported changing laundering practices as a result of odour in clothing. Of those who altered their laundering behaviour, respondents were less likely to use cold water and more likely to use hot water to wash odorous clothing compared with how they would wash a typical load of laundry. Approximately one-third of respondents dry odorous clothing differently and were less likely to dry by machine. Therefore, odour build-up in clothing may only play a minor role on sustainable behaviour; but when odour does affect a change it can lead to less sustainable laundering practices.